2018
DOI: 10.1186/s13073-018-0566-x
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants in SOX17 are associated with pulmonary arterial hypertension with congenital heart disease

Abstract: BackgroundPulmonary arterial hypertension (PAH) is a rare disease characterized by distinctive changes in pulmonary arterioles that lead to progressive pulmonary arterial pressures, right-sided heart failure, and a high mortality rate. Up to 30% of adult and 75% of pediatric PAH cases are associated with congenital heart disease (PAH-CHD), and the underlying etiology is largely unknown. There are no known major risk genes for PAH-CHD.MethodsTo identify novel genetic causes of PAH-CHD, we performed whole exome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 78 publications
(84 reference statements)
7
144
0
Order By: Relevance
“…GDF2 encodes a well-characterized ligand for BMPR2, and these data further confirm an important role for GDF2 in IPAH, as well as other PAH subclasses. Similar to the UK cohort, as well as our previous report of a cohort enriched in APAH-CHD cases 22 , we observed a low frequency of SOX17 variants (0.4%) in the PAH Biobank likely due, at least in part, to the paucity of APAH-CHD cases in both Biobank cohorts. Interestingly, a genome-wide association study of common SNPs involving both the PAH Biobank and the UK NIHR BioResource -Rare Diseases PAH Study identified SNPs in a putative endothelial-acting enhancer region of SOX17 in PAH 39 , suggesting that common variants may play an important role in susceptibility to PAH.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…GDF2 encodes a well-characterized ligand for BMPR2, and these data further confirm an important role for GDF2 in IPAH, as well as other PAH subclasses. Similar to the UK cohort, as well as our previous report of a cohort enriched in APAH-CHD cases 22 , we observed a low frequency of SOX17 variants (0.4%) in the PAH Biobank likely due, at least in part, to the paucity of APAH-CHD cases in both Biobank cohorts. Interestingly, a genome-wide association study of common SNPs involving both the PAH Biobank and the UK NIHR BioResource -Rare Diseases PAH Study identified SNPs in a putative endothelial-acting enhancer region of SOX17 in PAH 39 , suggesting that common variants may play an important role in susceptibility to PAH.…”
Section: Discussionsupporting
confidence: 89%
“…The data and resources are made available to the research community for hypothesis-driven projects via an application process (www.pahbiobank.org). A subset including 183 affected participants were included in previous publications from our group 14,20,22 . MLPA was performed with 100 ng of genomic DNA according to manufacturer's instructions using the P093 Salsa MLPA probe sets (MRC-Holland, Amsterdam, The Netherlands).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has identified SOX17 as a contributor to CHD associated with pulmonary hypertension as well as isolated and familial pulmonary hypertension (Zhu et al, 2018). SOX17 is a transcriptional target of GATA4, and it inhibits signaling in the WNT/B-catenin pathway involved in cardiac development (Holtzinger, Rosenfeld, & Evans, 2010;Zorn et al, 1999).…”
Section: Transcription Factorsmentioning
confidence: 99%
“…Nevertheless, the presence of a mutation in the context of PAH-CHD could predispose for or accelerate progressive, thus irreversible disease. Mutations in BMPR2,48 49 and recently in the transcription factor Sox17,50 have been associated with PAH in CHD specifically. Whether this provides sufficient rationale to screen for these variants in the assessment of PAH reversibility remains to be determined.…”
Section: Structural Functional and Molecular Assessment Of The Pulmomentioning
confidence: 99%